Histological and Histochemical Studies on the Nasal Cavity of the Young Pigs (Sus scrofa) - Parkash, Tej (Indian Journal of Veterinary Anatomy, 2019)
The present study was conducted on six local mixed breed pigs of 8-10 months age to study the histology and histochemistry of the nasal cavity. Histologically the nasal cavity was lined with three different types of epithelium i.e. stratified squamous, pseudostratified ciliated columnar and olfactory epithelium lining thevestibular, respiratory and olfactory regions, respectively. The dorsal and ventral nasal turbinates and major portion of the ethmoturbinates were lined with the pseudostratified ciliated columnar epithelium with PAS positive goblet cells. Follicle associated epithelium was observed in the epithelium of caudal part of dorsal nasal turbinate, rostral, middle and caudal portions of ventral nasal turbinate. Predominantly, mucous glands present in the propria submucosa were strongly PAS positive. The vascularity decreased cranio-caudally in the dorsalnasal turbinate while it was reverse in the ventral nasal turbinate. The caudal portion of the ethmoturbinates adjacent to the cribriform plate of the ethmoid bone was lined by the olfactory epithelium. The olfactory mucosa contained mucous type of Bowman’s glands and increased number of nerve bundles.